Migration of Pigtail Biliary Stent through Surface of the Left Lobe of Liver - Shah, Bhavik Bharat; Goenka, Usha; Banerjee, Debashish; Rai, Vijay; Goenka, Mahesh Kumar (Journal of Digestive Endoscopy, 2018)
We report a rare case of a patient of choledocholithiasis who underwent CBD stone removal with pigtail biliary stenting four year back, presenting with proximal migration of stent piercing the left lobe of liver. The stent was removed at laparotomy, by doing hepatotomy. We discuss this unreported case of proximal migration of pigtail biliary stent through surface of left lobe of liver.
Keywords: Hepatotomy; left lobe of liver; migration; pigtail biliary stent